Diagnostics of Wooden Poles Situated in the Open - Air Museum Using Sonic Tomography - Makýš Oto; Krušinský Peter; Korenková Renáta; Šrobárová Dominika (Civil and Environmental Engineering, 2018)
The paper deals with the lifetime of wooden poles, situated in the archaeological open-air museum Liptovská Mara - Havránok, which were erected outdoors about 12 years ago. It is aimed at diagnosing their condition using sonic tomography. The poles differ from each other in the location, anchorage, and positioning in terms of the terrain slope. Investigation was focused on the free-standing poles (quasi sacrifice poles) and the poles that are part of the fortification (gates and walls). Measurements were carried out using the device Fakopp ArborSonic 3D Sonic Tomograph that has 18 sensors. It measures the sonic response (sound velocity) in a tree stem. Sound wave velocity within sound wood depends on its species, moisture content, and the direction of measurement. Measurements brought remarkable results.